A New Business Process and Outcome Oriented Corporate Social Responsibility Index for Islamic Banking - Alamer, Abdullah Rajeh Ali; Salamon, Hussin Bin; Qureshi, Muhammad Imran; Rasli, Amran Md. (International Journal of Economics and Financial Issues, 2015)
This article has answered on two questions; what the process-outcome weight ratio for oriented outcome should be? The second question is: What are the items would be reflected elements under dimensions of both sides? In logic thinking, the used corporate social responsibility (CSR) dimensions of Islamic banks (IBs) have different impacts on the society as result for that these dimensions should be different. There still is very lack in using appropriate weights of dimensions to measure of CSR in IB. By redistribution of the dimensions to two types; business process dimensions (BPDs) and oriented outcome dimensions (OODs) then give each type specific weight to suit their consequence on the CSR's level in IBs. From 115 items, 23 sub-dimensions, and 7 dimensions that have taken from 18 articles since 2005 until 2013, this article has selected 16 items, 9 sub-dimensions, and 5 dimensions. Only Mohammed et al. (2008) built an index has different weights of the CSR's dimensions based on several academic experts in IB. The dimensions' weights has been calculated based on weights of Mohammed et al (2008) in which ratio of BPDs and OODs has been 54 and 46 respectively. Keywords: Corporate Social Responsibility,; Business Process; Oriented Outcome Dimensions JEL Classifications: K40